INTEGRASI EVENT OLAHRAGA TRADISIONAL DALAM PEMBELAJARAN PJOK SEBAGAI UPAYA PELESTARIAN BUDAYA DAN DAYA TARIK WISATA PADA SDN 98 KECEMATAN DENDANG - Dwiyono Fitrianto; Reza Hadinata; Wawan Junresti Daya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the declining interest of students in traditional sports due to the dominance of modern games and the development of digital technology. This situation has the potential to reduce students' physical activity and weaken their understanding of local cultural values. Traditional sports, however, have educational, social, and cultural values ​​that are crucial for character development in students. Therefore, integrating traditional sporting events into Physical Education, Sports, and Health (PJOK) lessons is seen as a strategic effort to preserve culture while increasing the attractiveness of culture-based tourism in the school environment.This study aims to analyze the process of integrating traditional sporting events into PJOK lessons and examine its impact on cultural preservation and the potential for local tourism development. The study used a qualitative approach with a descriptive interpretive design. The research subjects consisted of PJOK teachers, the principal, and students at SDN 98 in Dendang District. Data were collected through in-depth interviews, observations, and documentation studies. Data were then analyzed using the Miles and Huberman interactive analysis model, which includes data reduction, data presentation, and conclusion drawing. The research results show that integrating traditional sports events into physical education (PJOK) learning can increase student participation in physical activity, foster awareness and pride in local culture, and have the potential to serve as a cultural promotional medium that supports the development of tourism attractions based on local wisdom.